Predictive factors of pancreatic necrosectomy following percutaneous catheter drainage as a primary treatment of patients with infected necrotizing pancreatitis - Cao, Xi (Exp Ther Med, 2017)
Pancreatic necrosectomy (PN) following percutaneous catheter drainage (PCD) is an effective method of treating patients with necrotizing pancreatitis, however, the predictive factors for PN after PCD have not yet been identified. A total of 74 patients with suspected infected necrotizing pancreatitis (INP) and peripancreatic fluid collection were enrolled in the current study between October 2010 and October 2015. These patients received ultrasound or computer topography guided PCD followed by PN. Patients were divided into two groups: i) A PCD-alone group (n=32) and ii) a PCD+necrosectomy group (n=42). Multivariate analysis revealed that reduction of fluid collection after PCD (P=0.021), maximum extent of peripancreatic necrosis (P=0.019) and multiple organ failure (P=0.017) were predictors of PN following PCD. A prediction model was produced to evaluate the aforementioned factors and indicated that the area under the receiver operating characteristic curve was 0.827. The probability of successful PCD was determined using a prognostic nomogram. Thus, the results of the current study demonstrated that a reduction of fluid collection by <50% following PCD, a maximum extent of peripancreatic necrosis of >50% and multiple organ failure are effective predictors of necrosectomy in patients with INP following PCD failure.